Separation Of Copper And Chromium Metal In Ultrabasic Rocks From Top Of Manoapa Region, Subdistrict Of Lasusua Southeast Sulawesi By Ligand of 2 - (Aminometil) Pyridine - Harimu, La; Hasria, Hasria; Intan, Putri (Indonesian Journal of Chemical Research, 2013)
Study on separation of ions chromium metal and copper in ultrabasic material located in the village to of Monapa subdistrict Lasusua Regency Kolaka Utara Province Sulawesi Tenggara was conducted. The aim of this study was to determine the ability of the ligand 2-(aminometil) pyridine to separate chromium metals and copper to pure metals and its application to separate the chromium metals (Cr) and copper (Cu) in ultrabasic material from the village of Puncak Monapa subdistrict Lasusua Regency Kolaka Utara Province Sulawesi Tenggara by means of extraction method. The concentration of ions chromium metal (Cr) and copper (Cu) of the pure metals are extracted respectively 10 ppm, and the concentration of the ligand 2-(aminometil) pyridine is 10 ppm. For concentration ion chromium metal (Cr) and copper (Cu) in ultrabasic material with 20x and 30x dilution is 8.3875 and 1.3590 and 3.50 ppm and 2,001 ppm for the ions copper metal (Cu). Results of this research shomush that the ability of ligand 2-(aminometil) pyridine for extracting chromium metals (Cr) and copper (Cu) for a single pure metal has a percent extraction (%E) are respectively 79.375 % and 82.37 %. Separation ability of ions chromium metal (Cr) and ions copper (Cu) mixed are 77.625% and 79.96%. For its application in separating ions chromium metal (Cr) and copper (Cu) in ultrabasic material to 20 time dilution extraction are 74.51% and 71.35%, and 30 time dilution are 69.28% and 69.71%. Based on the results of the study ligand 2-(aminometil) pyridine is relatively better for ions copper metal (Cu) for extraction ions of pure metal and relatively similar to ultrabasic material.